1993
DOI: 10.1111/j.1432-1033.1993.tb17766.x
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction, purification and characterization of the bacterioferritin of Escherichia coli and a C‐terminally extended variant

Abstract: The bacterioferritin (BFR) of Escherichia coli is an iron-sequestering haemoprotein composed of 24 identical polypeptide chains forming an approximately spherical protein shell with a central iron-storage cavity. BFR and BFR-A, a variant with a 14-residue C-terminal extension, have been amplified (120-fold and 50-fold, respectively), purified by a new procedure and characterized. The overproduced BFR exhibited properties similar to those of natural BFR, but the iron content (25-75 non-haem Fe atoms/molecule) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 49 publications
5
50
0
Order By: Relevance
“…This is especially significant since it has been recently demonstrated that a solution of EcBFR contains, even if in a minute quantity, dimers as well as the 24-mer protein (Andrews, Smith, Hawkins, Williams & Harrison, 1993). It has to be recognized that the molecule of BFR that we report is very surprising and raises the question of how such a water-soluble molecule can be attached to the membrane of the cell and yet sediment with membranes on cell disruption (Keilin & Harpley, 1941;Deeb & Hager, 1964).…”
Section: Discussionmentioning
confidence: 66%
“…This is especially significant since it has been recently demonstrated that a solution of EcBFR contains, even if in a minute quantity, dimers as well as the 24-mer protein (Andrews, Smith, Hawkins, Williams & Harrison, 1993). It has to be recognized that the molecule of BFR that we report is very surprising and raises the question of how such a water-soluble molecule can be attached to the membrane of the cell and yet sediment with membranes on cell disruption (Keilin & Harpley, 1941;Deeb & Hager, 1964).…”
Section: Discussionmentioning
confidence: 66%
“…Based on its similarity to other ferritins and its importance in the B. fragilis oxidative stress response, we presume that the dodecameric assembly is physiologically relevant. Importantly, recent literature for several other members of the ferritin superfamily also indicates easy dissociation into dimers or monomers in vitro (4,8,12,14,20,30). One possible explanation for BfDPSL is that assembly might be facilitated by other proteins in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is an essential cofactor of many enzymes, and bacteria have evolved a range of strategies to acquire and store iron, which is often not bioavailable in the environment. E. coli possesses two main iron storage proteins: bacterioferritin and ferritin (4). Bacterioferritin, whose precise function is still unclear (1), is induced during slow growth or at the transition to stationary phase, consistent with its regulation by rpoS.…”
Section: Vol 186 2004 Gene Expression At the Onset Of Stationary Phmentioning
confidence: 96%